EDUKASI PERILAKU CERDIK PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BANJAR 1 - Maharani, Indy Zafira; Yuniarti, Mellynia; Sari, Neng Ratna; Aulia, Tri Wahyuni; Farsida, Farsida; Syahniar, Rike (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
In general, hypertension is an asymptomatic condition, namely abnormally high pressure in the arteries causing an increased risk of stroke, heart failure, heart attack, and kidney damage which is the leading cause of chronic heart failure. An unhealthy lifestyle and a history of hypertension can trigger hypertension. The community has an essential role in preventing non-communicable diseases such as hypertension and fostering a culture of clean and healthy living behavior (PHBS) in the community. PHBS on the prevention of non-communicable diseases is implemented through the